Filsafat Manusia dalam Pandangan Drijarkara - Mahamida, Luthfin (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2024)
Humans do not automatically become human after their birth. Birth is the first step for humans to become acquainted with the world, even though they are not fully aware, at least humans have recognition of their existence. This means that, in its form as an entity consisting of bones covered in flesh and skin with all its characteristics, humans are generally able to be recognized and accepted by other humans. This shows that the 'new' human is ready to face the world with all its dynamics.This writing discusses 3 issues, which emphasizes knowing 3 drijarkara views in understanding humans. Regarding biography, humans have bodies, humans have spiritual existence, as well as human relationships with other humans, which are then understood as human dynamics. This writing uses the library study method. In obtaining knowledge, we use the tools of description, interpretation and coherence.